Type I interferon pathway activation across the antiphospholipid syndrome spectrum: associations with disease subsets and systemic antiphospholipid syndrome presentation - Cecchi, Irene; Radin, Massimo; Barinotti, Alice; Foddai, Silvia Grazietta; Menegatti, Elisa; Roccatello, Dario; Suárez, Ana; Sciascia, Savino; Rodríguez-Carrio, Javier (Frontiers in Immunology, 2024)
Introduction. While type I interferon (IFN-I) pathway is crucial in autoimmunity, its role in antiphospholipid antibodies (aPL) positive subjects, including aPL carriers and antiphospholipid syndrome (APS) patients, is poorly understood. This study aims at characterizing IFN-I pathway activation within the spectrum of aPL+ subsets.Methods. A total of 112 patients [29 aPL carriers, 31 PAPS, 25 SAPS, 27 SLE patients without aPL, and 44 healthy controls (HCs)], were recruited. IFI6, IFI44, IFI44L, MX1, IFI27, OAS1 and RSAD2 gene expression was evaluated in whole blood, and a composite index (IFN score) was calculated.Results. An overall activation of the IFN-I pathway was observed across the entire APS spectrum, with differences among genes based on the specific disease subset. The composite score revealed quantitative differences across subsets, being elevated in aPL carriers and PAPS patients compared to HCs (both p<0.050) and increasing in SAPS (p<0.010) and SLE patients (p<0.001). Unsupervised cluster analysis identified three clusters and correspondence analyses revealed differences in clusters usage across APS subsets (p<0.001). Network analysis revealed different patterns characterizing different subsets. The associations between IFN-I pathway activation and clinical outcomes differed across APS subsets. Although no differences in gene expression were observed in systemic APS, network analyses revealed specific gene-gene patterns, and a distinct distribution of the clusters previously identified was noted (p=0.002).Qualitative and quantitative differences across the APS spectrum can be identified, leading to the identification of distinct IFN-I signatures with different clinical value beyond traditional categorization.